Is muscular strength a critical physical attribute for the apprehension of a simulated non-compliant suspect?. Issue 9 (2nd September 2021) - Delbridge, Kent; Caldwell, Joanne; Middleton, Kane; Drain, Jace R.; Hayes, Adam; Burdon, Catriona A.; Groeller, Herbert
Abstract: This investigation determined the influence of technique and experience on arm retraction force required to apprehend a non-compliant suspect. Phase-One: Nine experienced RAAF military-police completed four apprehension simulations, peak arm retraction force was measured; i) Control(CON ), ii) Pressure-Point(PP ), iii) Targeted-Striking(TS ) and iv) 2-Person(2Per ) techniques. Phase-Two: Experienced (EXP, n  = 8) or Inexperienced (INEXP, n  = 22) military-police completed CON, PP and Pressure-Point + Coaching(PP + C ). Strength was assessed in INEXP . EXP produced more force (178.7 N ± 25.9) than INEXP during CON, but no participant successfully apprehended the suspect. All EXP were successful with PP, arm retraction force 357 N (CI: 233.7, 480.2) was lower compared to CON, but no difference was observed between PP and CON for INEXP . PP + C, 82% of INEXP were successful, force declined 138.2 N (CI: 67.8, 208.5) compared to CON . All EXP required PP for successful apprehension. INEXP required PP + C for apprehension success. Muscular strength had a limited relationship with arm retraction force. Practitioner summary: For law enforcement personnel, apprehension of a suspect is a critical and physically demanding task, where success is associated with muscular strength and technique. We observed success in the apprehension of a simulated suspect by military law enforcement personnel was primarily determined by participant skill and experience and not muscular strength.